2008
DOI: 10.1071/ea07256
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from beef cattle - a comparison of paddock- and animal-scale measurements

Abstract: Methane (CH4) emissions from a herd of 58 grazing cattle were determined in a field experiment using paddock-scale (micrometeorological) methods. The emissions were also measured daily from each animal, using the sulfur hexafluoride tracer method. The paddock-scale methods exploit how the gas, once emitted from the cattle, is transported and dispersed by the wind. Hence, the emission rate may be calculated from measurements of windspeed, wind direction and turbulence statistics, as well as CH4 concentration up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 15 publications
2
47
1
Order By: Relevance
“…Direct measurements of enteric CH 4 emissions are commonly made on individual animals using open-circuit respiration chambers Kreuzer, 2006, 2008) or the SF 6 tracer technique (Lassey, 2007;Pinares-Patiño et al, 2007). Both methods are labor intensive and thus are usually applied only for rather short time intervals (several days).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurements of enteric CH 4 emissions are commonly made on individual animals using open-circuit respiration chambers Kreuzer, 2006, 2008) or the SF 6 tracer technique (Lassey, 2007;Pinares-Patiño et al, 2007). Both methods are labor intensive and thus are usually applied only for rather short time intervals (several days).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are based on average concentration measurements: backward Lagrangian stochastic 3926 R. Felber et al: Eddy covariance methane flux measurements over a grazed pasture dispersion, mass balance for entire paddocks, and gradient methods (Harper et al, 1999;Laubach et al, 2008;Leuning et al, 1999;McGinn et al, 2011). They have in common that they integrate over a group of animals and are usually applied over specifically designed relatively small fenced plots.…”
Section: Introductionmentioning
confidence: 99%
“…Laubach et al (2008) reported a good fit of CH 4 emissions from cattle in small paddocks when using the BLS, FG and IHF techniques (plus an enteric tracer technique) simultaneously, provided that a minimum separation between the paddock and sensor location exists when using the FG and IHF techniques. In their study, using 22 m separation, the BLS emissions were correlated with IHF (R 2 5 0.85) and FG (R 2 5 0.75); however, the BLS emissions were 20% higher than the two techniques.…”
Section: Accuracy Of Micrometeorological Techniquesmentioning
confidence: 96%
“…Since then, this technique has also been applied to grazing cattle (Laubach et al, 2008). Like other micrometeorological techniques, FG is best suited to operate in the fully adjusted IBL; else a footprint model (Vesala et al, 2008) must be used to gauge the influence of the source configuration on the calculated emission (see the discussion below).…”
Section: Fgmentioning
confidence: 99%
See 1 more Smart Citation